2022
DOI: 10.1155/2022/4971977
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Flora of South Sulawesi, Forest Vegetation, and Karst Areas as Bundle Dyeing on Silk Fabrics

Abstract: The development of dyeing frm natural substances for silk fabrics has been rapidly growing in recent years. This study aimed to explore the plant species prodsucing unique dyes and patterns on silk fabrics. The flowers and leaves of some plant species found at the research sites were assayed for their color and shape expression on the fabrics. The dyeing technique applied was the bundle dyeing or ecoprinting technique on the fabric’s surface with mordant alum and myrobalan. We obtained 297 plants consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Based on the literature review, Indonesia has many plants that can be used as natural dyes. Research on using plants as natural dyes has been conducted by [8], who found as many as 297 plants in South Sulawesi that can be used as dyes for silk fabrics. In addition, Table 1 shows various plants that can be used as natural dyes.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the literature review, Indonesia has many plants that can be used as natural dyes. Research on using plants as natural dyes has been conducted by [8], who found as many as 297 plants in South Sulawesi that can be used as dyes for silk fabrics. In addition, Table 1 shows various plants that can be used as natural dyes.…”
Section: Resultsmentioning
confidence: 99%
“…The entire ecoprint research process is considered more environmentally friendly, therefore the ecoprint technique is increasingly popular not only among fashion designers, but also the general public such as artists, homemade handcraft craftsmen, and so on. The common ecoprint 1203 (2023) 012020 IOP Publishing doi:10.1088/1755-1315/1203/1/012020 2 technique uses fabrics with cellulose and protein base materials such as silk, cotton and linen [4]. Since ecoprint technique uses many natural elements, it will be best to also uses fabrics from natural fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The ecoprint technique as a technique for utilizing natural colors by transferring certain colors and shapes to fabric through direct contact is starting to be in great demand in the industrial world (Nuraeni et al, 2022;(Suharsono et al, 2022). The ecoprint technique has been widely used in the textile industry (Sedjati & Sari, 2019), including the Kampung Sabbeta silk industry.…”
Section: Introductionmentioning
confidence: 99%